Probing characteristics of cancer cells cultured on engineered platforms simulating different microenvironments - Jo, Yeonho; Choi, Nakwon; Kim, Hong Nam; Choi, Jonghoon (TAYLOR & FRANCIS LTD, 2018)
In this study, we demonstrate cell culture platforms that can provide a microenvironment similar to in vivo conditions so that in vivo-compatible drug testing results can be obtained from the in vitro experiments. To realize such in vivo microenvironment-mimetic platforms, different culture platforms such as a three-dimensional (3D) cell aggregate film, fluidic environment within a microfluidic system or extracellular matrix (ECM) coating were established. The tumor cell growth rate and sensitivity to doxorubicin (DOX) were studied using the glioblastoma cell line T98G. When 3D spheroids were cultured, they grew significantly slower than under other culture conditions. When the cells were treated with DOX, the anticancer drug could not efficiently penetrate the 3D spheroids to inhibit cell growth. When cultured on the Matrigel-coated culture vessel, T98G cells grew even in the presence of DOX, demonstrating chemoresistance. Nonetheless, in the 2D culture plate and in the microfluidic chip, cell growth decreased with DOX treatment and the binding ability was lost. These results indicate that the cells reacted differently to the same anticancer drug depending on the culture microenvironment. We believe that the development of a more physiologically relevant tumor cell culture platform will lead to more reliable antitumor drug responses.
Keywords: DEVELOPMENT SUCCESS RATES; TUMOR MICROENVIRONMENT; CLINICAL-TRIALS; PHARMACEUTICAL-INDUSTRY; ANIMAL-MODELS; IN-VIVO; INNOVATION; CHALLENGES; RESISTANCE; SPHEROIDS